PENILAIAN KINERJA BERBASIS VALUE FOR MONEY ATAS PENERIMAAN PENDAPATAN ASLI DAERAH KABUPATEN TABANAN - Purnomo, Agus; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
Public sector performance measurement is essential for assessing the accountability of the organization and can result in better public services. Demands appear to be public sector organizations pay attention to value for money in carrying out its activities. Value for money is the concept of managing public sector organization based on three elements, namely the economy, efficiency, and effectiveness. This study aim to know how the performance of Tabanan District Revenue Office on receipt of the original income in years 2010-2013 based on economic variables, efficiency, and effectiveness. The analysis technique used in this study is a quantitative and qualitative analysis techniques. The results show that, the performance of the Department of Revenue district of Tabanan when viewed from the economic criteria of fiscal year 2010 to the year 2013 has increased every year, and very economical categorized as level of economic ratio is above 100%. Terms of the efficiency for the original income of the fiscal year 2010 to the year 2013 categorized as very efficient because efficiency ratio of less than 60%. Terms of the effectiveness of performance Tabanan District Revenue Office for Regional Revenue in 2010 until 2013 has fluctuated but is still considered very effective due to its effectiveness ratios above 100%.
Keywords: value for money; original income districts